Adapting Crew Resource Management for Training in Unmanned Operations. (September 2022) - Kreischer, Noah; Sebok, Angelia; Orchosky, Lauren; "Roy" Rogers, D.A.
As automation is increasingly used on the flight deck and in unmanned aerial operations, the concept of "automation as a team member" becomes increasingly important. In addition to taking over certain aviation tasks there is a need to plan and train for the roles taken by automation. While training does exist to teach the flight crew how to interact with automation, the concept of automation as a team member is ill defined. In this work, we used the framework provided by Crew Resource Management (CRM) to begin addressing the needs for developing scenario-based training that address this gap.